Strategies reimagined: SDG-driven solutions for combating global desertification - Xunming Wang; Xin Geng; Fubao Sun; Mengyao Han; Fahu Chen; Shengqian Chen; Josep Peñuelas; Lei Gao; Brett A. Bryan; Changjia Li; Lindsay C. Stringer; Jiansheng Ye; et al. (Proceedings of the National Academy of Sciences, 2026)
Desertification threatens 24% of the world’s land area across 126 countries and affects 35% of the global population. However, mainstream global efforts to combat desertification prioritize short-term vegetation greening over addressing resource constraints and local livelihoods, posing hidden challenges to long-term Sustainable Development Goals (SDGs) attainment. Here, we evaluated the socioeconomic trade-offs of China’s long-standing desertification reversal strategies and explored the potential benefits of innovative agricultural practices using high-resolution suitability models for major crops and cultivated pasture. Compared with a no-intervention baseline, continuing the Grain-for-Green Program and grazing exclusion under projected 2023–2050 warming and wetting trends would lead to reductions of up to 54 to 55% in grain output, 81% in livestock production, and 61% in agricultural income. Conversely, strategies emphasizing pasture cultivation and crop switching could substantially lower national expenditures on combating desertification while restoring ecosystems, enhancing agricultural productivity and incomes, and conserving water resources. These benefits would contribute 0.7%, 9.8%, and 3.8% toward global progress on SDG 1 (no poverty), SDG 2 (zero hunger), and SDG 6 (clean water and sanitation), respectively, while exhibiting trade-offs across multiple SDGs. This study provides a reimagined strategy framework for combating global desertification and promoting sustainable development in vulnerable arid regions worldwide.